2024
DOI: 10.1101/2024.06.04.597289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diet drives performance trade-offs along Atlantic salmon ontology

Tutku Aykanat,
Jan Arge Jacobsen,
Kjetil Hindar

Abstract: Understanding the ecological basis of life-history trade-offs is fundamental for predictive ecology. Contrary to the theory, the documentation of trade-offs between life-history traits is mostly lacking in the wild, which is suggested to be masked by individual differences in resource acquisition. However, this effect has not been empirically demonstrated in free-living organisms. By quantifying the diet composition of wild Atlantic salmon sampled from marine feeding grounds in the Northeast Atlantic Ocean, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
2
2
0
Order By: Relevance
“…However, foraging outcome was meaningfully different within vgll3 genotypes and sexes across sea-ages, whereby vgll3 LL genotype and females consumed a higher number of fish in the 1SW age group with marginal and significant age-dependent changes for vgll3 and sex, respectively. This pattern is concordant with the notion that fish acquisition may not be an efficient energy source for 1SW for early maturation (Aykanat et al 2024), and further highlights resource acquisition as a potential ecological function that links maturation timing to genetic polymorphisms in the vgll3 locus, and sex. However, caution is required when interpreting the results for the fish model, as the model fit deviates from the linear model assumptions and convergence for alternative parameterization options was not achieved.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, foraging outcome was meaningfully different within vgll3 genotypes and sexes across sea-ages, whereby vgll3 LL genotype and females consumed a higher number of fish in the 1SW age group with marginal and significant age-dependent changes for vgll3 and sex, respectively. This pattern is concordant with the notion that fish acquisition may not be an efficient energy source for 1SW for early maturation (Aykanat et al 2024), and further highlights resource acquisition as a potential ecological function that links maturation timing to genetic polymorphisms in the vgll3 locus, and sex. However, caution is required when interpreting the results for the fish model, as the model fit deviates from the linear model assumptions and convergence for alternative parameterization options was not achieved.…”
Section: Discussionsupporting
confidence: 80%
“…However, it is not clear if this effect is manifested via condition factor, a primary phenotypic trait associated with maturation timing (Thorpe et al, 1998) which is linked to vgll3 during precocious male maturation (Debes et al, 2021). Using the same dataset, Aykanat et al (2024) showed an ontogenetic trade-off between condition factor and diet composition, whereby an increased crustaceans diet increases the condition factor in younger sea-age groups but decreases it in the older age groups, while fish diet exhibited the opposite effect. To explore whether vgll3 or sex was linked to age-dependent differences in the condition factor, and consistently so with the expected maturation patterns, we implemented a linear mixed model with a Gaussian error structure using condition factor as the response variable, and using a similar covariate structure as above (except that sea-age was modeled categorically which was more parsimonious than a numeric model).…”
Section: Discussionmentioning
confidence: 95%
“…However, foraging outcome was meaningfully different within vgll3 genotypes and sexes across sea-ages, whereby vgll3 LL genotype and females consumed a higher number of fish in the 1SW age group with marginal and significant age-dependent changes for vgll3 and sex, respectively. This pattern is concordant with the notion that fish acquisition may not be an efficient energy source for 1SW for early maturation (Aykanat et al, 2024a), and further highlights resource acquisition as a potential ecological function that links maturation timing to genetic polymorphisms in the vgll3 locus, and sex. However, caution is required when interpreting the results for the fish model, as the model fit deviates from the linear model assumptions and convergence for alternative parameterization options was not achieved.…”
Section: Discussionsupporting
confidence: 80%
“…However, it is not clear whether this effect is manifested via condition factor, a primary phenotypic trait associated with maturation timing (Thorpe et al, 1998) which is linked to vgll3 during precocious male maturation (Debes et al, 2021). Using the same dataset, Aykanat et al (2024a) showed an ontogenetic tradeoff between condition factor and diet composition, whereby an increased crustaceans diet increases the condition factor in younger sea-age groups but decreases it in the older age groups, while fish diet exhibited the opposite effect. To explore whether vgll3 or sex was linked to age-dependent differences in the condition factor, and consistently so with the expected maturation patterns, we implemented a linear mixed model with a Gaussian error structure using condition factor as the response variable, and using a similar covariate structure as above (except that sea-age was modelled categorically which was more parsimonious than a numeric model).…”
Section: Discussionmentioning
confidence: 99%